Influence of processing factors on the stability of model mayonnaise with whole egg during long-term storage. Issue 4 (3rd April 2017) - Ariizumi, Masahiro; Kubo, Megumi; Handa, Akihiro; Hayakawa, Takashi; Matsumiya, Kentaro; Matsumura, Yasuki
Abstract: Mayonnaise-like oil-in-water emulsions with different stabilities—evaluated from the degree of macroscopic defects, e.g., syneresis—were prepared by different formulations and processing conditions (egg yolk weight, homogenizer speed, and vegetable oil temperature). Emulsions prepared with lower egg yolk content were destabilized for shorter periods. The long-term stability of emulsions was weakly related to initial properties, e.g., oil droplet distribution and protein coverage at the interface. Protein aggregation between oil droplets was observed and would be responsible for the instability of emulsions exhibited by the appearance defects. SDS-PAGE results for adsorbed and unadsorbed proteins at the O/W interface suggested that predominant constituents adsorbed onto the interface were egg white proteins as compared with egg yolk components when the amount of added egg yolk was low. In present condition, egg white proteins adsorbed at the O/W interface could be a bridge of neighboring oil droplets thereby causing flocculation in emulsions. Abstract : :